Methotrexate is not superior to placebo in maintaining steroid-free response or remission in ulcerative colitis - Herfarth, Hans (Gastroenterology, 2018)
BACKGROUND & AIMS: Parenteral methotrexate induces clinical remission but not endoscopic improvement of mucosal inflammation in patients with ulcerative colitis (UC). We performed a randomized, placebo-controlled trial to assess the efficacy of parenteral methotrexate in maintaining steroid-free response or remission in patients with UC following induction therapy with methotrexate and steroids. METHODS: We performed a 48-week trial, from February 2012 through May 2016, of 179 patients with active UC (Mayo score 6–12 with endoscopy subscore ≥2) despite previous conventional or biological therapy. The study comprised a 16-week open-label methotrexate induction period followed by a 32-week double-blind placebo-controlled maintenance period. Patients were given subcutaneous methotrexate (25 mg/week) and a 12-week steroid taper. At week 16, steroid-free responders were randomly assigned to groups that either continued methotrexate (25 mg/week, n=44) or were given placebo (n=40) until week 48. We compared the efficacy of treatment by analyzing the proportion of patients who remained relapse free and were in remission at week 48 without use of steroids or other medications to control disease activity. RESULTS: Ninety-one patients (51%) achieved response at week 16, and 84 patients were included in the maintenance period study. During this period, 60% of patients in the placebo group (24/40) and 66% in the methotrexate group (29/44) had a relapse of UC (P=.75). At week 48, 30% of patients in the placebo group (12/40) and 27% of patients in the methotrexate group (12/44) were in steroid-free clinical remission without need for additional therapies (P=.86). No new safety signals for methotrexate were detected. CONCLUSIONS: Parenteral methotrexate (25 mg/week) was not superior to placebo in preventing relapses of UC in patients who achieved steroid-free response during induction therapy. CLINICALTRIALS.GOV ID NO: NCT01393405